ANALISIS YURIDIS TANGGUNG JAWAB PARA PIHAK DALAM PERJANJIAN JUAL BELI TANAH DENGAN ANGSURAN YANG DIBUAT DI BAWAH TANGAN - ERLIASNA BR. TARIGAN (PREMISE LAW JURNAL, 2016)
A contract on the acquisition of land with buildings on it is made underhandedly, this kind of contract is basically unrecognized in the Indonesian agrarian system and in the Civil Code. The research used descriptive analytic and judicial normative method. The conclusions of the research were as follows: a contract on the acquisition of land for constructing buildings on it is a standard contract, the responsibility which will be taken by the buyer when he is default is fine and time limit, while the seller is responsible for limitation, and the acquisition of land with buildings on it only has legal force of material evidence. It is recommended that the parties concerned pay specific attention to the right buying and selling of land, it should be signed by a Subdistrict head and village heads, and should be a firm regulation and controllers on standard contracts which have specific clauses. Keywords: Standard Contract, Land, Responsibility, Evidence